PENGARUH GAYA KEPEMIMPINAN PATERNALISTIK TERHADAP KINERJA PEGAWAI DI BAGIAN OTONOMI DAERAH SEKRETARIAT KABUPATEN KUTAI TIMUR - Fl. Sudiran Akhmad Fadil Hidayat (ADMINISTRASI PUBLIK, 2017)
This study aims to know the influence of paternalistic leadership on the performanceof employees in the Regional Autonomy Division of the Regional Secretariat of East KutaiRegency, therefore the researcher formulates the hypothesis